MORPHOLOGICAL PATTERNS IN CHILDREN WITH GANGLION RELATED ENTERIC NEURONAL ABNORMALITIES - Henna, Nausheen; Nagi, Abdul H; Sheikh, Muhammad A; Shaukat, Mahmood (Journal of Ayub Medical College Abbottabad, 2011)
Background: Hirschsprung's Disease (HD) is a developmental disorder of enteric nervous system characterised by the absence of ganglion cells in submucosal (Meissner's) and myenteric (Aurbach's) plexuses of distal bowel. The purpose of the present study was to observe and report the morphological patterns of ganglion related enteric neuronal abnormalities in children presented with clinical features of (HD) in a Pakistani population. Methods: A total of 92 patients with clinical presentation of HD were enrolled between March 2009 and October 2009. Among them, 8 were excluded according to the exclusion criteria. After detailed history and physical examination, paraffin embedded H and E stained sections were prepared from the serial open biopsies from colorectum. The data was analysed using SPSS-17. Frequencies and percentages are given for qualitative variables. Non-parametric Binomial Chi-Square test was applied to observe within group associations and p<0.05 was considered statistically significant. Results: Among 84 patients, 13 (15.5%) proved to be normally ganglionic whereas 71 (84.5%) showed ganglion related enteric neuronal abnormalities namely isolated hypoganglionosis 9 (12.7%), immaturity of ganglion cells 9 (12.7%), isolated hyperganglionosis (IND Type B) 2 (2.8%) and Hirschsprung's disease 51 (71.8%). Among HD group, 34 (66.7%) belonged to isolated form and 17 (33.3%) showed combined ganglion related abnormalities. Conclusions: Hirschsprung's disease is common in Pakistani population, followed by hypoganglionosis, immaturity of ganglion cells and IND type B. The presence of hypertrophic nerve fibres was significant in HD, hyperganglionosis and hypoganglionosis, whereas, no hypertrophic nerve fibres were appreciated in immaturity of ganglion cell group. Keywords: Hirschsprung's disease (HD), hypoganglionosis, immaturity of ganglion cells (IGC), intestinal neuronal dysplasia (IND)